Pertumbuhan dan Produksi Rimpang Kencur (Kaempferia galanga L.) pada Ketinggian Tempat yang Berbeda - Subaryanti Subaryanti; Yohana Caecilia Sulistyaningsih; Dyah Iswantini; Triadiati Triadiati (Jurnal Ilmu Pertanian Indonesia, 2020)
Galanga (Kaempferia galanga L.) is one of the potential medicinal plants with high demand. Therefore, galanga cultivation was still quite promising. To obtain the optimum growth and high rhizome production, the superior galanga accessions are required. The optimal growth and high production of galanga accessions will be obtained if cultivated at the area with appropriate altitude. The purpose of the study was to obtain galanga accession with a better growth and high yield at the area with a suitable altitude. This study used split-plot design; altitude as a main plot and accession as a subplot. The location as a main plot consisted of altitudes of 214 and 780 masl. This study used seven accessions i.e., accession of PBG (Purbalingga), CLP (Cilacap), PWJ (Purworejo), KRA (Karanganyar), PCT (Pacitan), MAD (Madiun), and GAL2 (Galesia 2) as control. The results showed that different altitudes significantly affected the total chlorophyll content, stomatal conductance, transpiration rate, photosynthesis rate, dry weight, and rhizome yield. The number of leaves was influenced by altitude and accession of galanga. The interaction between altitude and accession of galanga significantly affected the leaf area and the soluble sugar concentration in the galanga rhizome. The rhizome yield at low altitude was higher than in high altitude. PBG (Purbalingga) and PWJ (Purworejo) accessions have the potential to be developed in locations with an altitude of 214 masl. Keywords: altitude, Kaempferia galanga, rhizome